PENGARUH DUE PROFESSIONAL CARE, INDEPENDENSI, PENGALAMAN KERJA DAN INTEGRITAS TERHADAP KUALITAS HASIL AUDIT APIP DALAM PENGAWASAN KEUANGAN DAERAH (Studi Empiris pada Inspektorat Provinsi Riau) - Nelda Pratiwi; Kirmizi Ritonga; Rusli - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to determinethe effect of due professional care, independency, work experience and integrity to the quality of the audit results. The study was conducted in Riau Provincial Inspectorate. The population is around the internal auditor in the Inspectorate of Riau province, amounting to 41 respondents. The sampling data of this study using census sampling technique in which all members of the population used as sampel. Data collection techniques in this study is in the form of a questionnaire,while the data analysis technique used is multiple regression analysis were processed with SPSS version 17 for windows. From partial regression test (t test) showed that due professional care,work experience and integrity significant effect on the quality of audit, while independency no significant effect on the quality of the audit results. Simultaneous regression test (F test) showed that all the independent variables simultaneously influence on the quality of the audit results. The magnitude of the effect that (Adjusted R2) by four variables together against the dependent variable 61.8%, while the remaining 38.2% is influenced by other variables not examined in this study. Researcher suggested for future research in order to add more variable and then to extend the population.Keywords: due professional care, independency, work experience, integrity, quality of audit result.